1994
DOI: 10.1002/hed.2880160107
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of frequency of pulmonary atelectasis in patients undergoing pectoralis major musculocutaneous flap reconstruction

Abstract: The incidence of pulmonary atelectasis following head and neck surgery is not well reported. This study retrospectively evaluated the incidence of pulmonary atelectasis in 161 head and neck cancer patients, with 152 being evaluable. There were 90 patients evaluated following pectoralis musculocutaneous flap reconstruction with their effective flap size and 71 nonflap patients as a control group. Clinical findings were correlated to radiographic scores. Of pectoralis musculocutaneous flap patients screened for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
2
4

Year Published

1995
1995
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 8 publications
2
28
2
4
Order By: Relevance
“…There was no difference in the atelectasis scores and categories between patients with rectus abdominis myocutaneous flaps and patients in the control group (Figure 2 and Figure 3, respectively). Arbitrarily, flaps with skin paddles greater than 120 cm 2 were considered large and were analyzed separately. Patients with large flaps demonstrated atelectasis 79% of the time compared with patients with smaller flaps, who demonstrated atelectasis 55% of the time.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…There was no difference in the atelectasis scores and categories between patients with rectus abdominis myocutaneous flaps and patients in the control group (Figure 2 and Figure 3, respectively). Arbitrarily, flaps with skin paddles greater than 120 cm 2 were considered large and were analyzed separately. Patients with large flaps demonstrated atelectasis 79% of the time compared with patients with smaller flaps, who demonstrated atelectasis 55% of the time.…”
Section: Resultsmentioning
confidence: 99%
“…Of these patients, 6.7% developed major atelectasis. Schuller et al 2 were unable to demonstrate an increased incidence of pulmonary atelectasis with pectoralis major myocutaneous flap reconstruction; however, they found that patients with PEPD exhibited a higher rate of pulmonary atelectasis. They also were unable to correlate between larger flaps and pulmonary atelectasis.…”
Section: Commentmentioning
confidence: 99%
See 3 more Smart Citations